METHODOLOGY OF ORGANIZATION AND QUALITY ASSESSMENT OF TRANSPORT AND LOGISTICS SERVICES MARKET - Narinbaevna, Irisbekova Mavluda; Hamidovich, Ziyavitdinov Habibullo (International Journal of Psychosocial Rehabilitation, 2020)
This article extensively covers the issues of establishing the transport and logistics services market and its impact on the development of national economy sectors. Cargo transportation - it is necessary to reduce cost and time costs and economically justify the transportation process. Consequently, this transportation function delivers faster, cheaper and less environmentally friendly, quality and integrity of cargo due to the need to reduce time, money, and environmental resources and the need to reduce logistics.